Công ước quốc tế về thiết lập quỹ quốc tế về bồi thường thiệt hại do ô nhiễm dầu 1971. (1971)
Tài liệu giới thiệu công ước quốc tế về thiết lập quỹ quốc tế về bồi thường thiệt hại do ô nhiễm dầu 1971.